KOMPOSISI HASIL TANGKAPAN PUKAT TERI (PURSE SEINE) SEBELUM DAN SESUDAH TENGAH MALAM DI DESA KWALA GEBANG KECAMATAN GEBANG KABUPATEN LANGKAT PROVINSI SUMATERA UTARA - Harry Kurniawan; Arthur Brown; Pareng Rengi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The research was conducted during of April 2016 in the village of kwalagebang Village gebang District of North Sumatra. The purpose of this study was to determine the composition of the catches of anchovy purse seine net which operated at the time before and after midnight. The method used a survey method. Results from the study showed that the after midnight operation period ( 00:00 till 04:00 ) broughthigher catches as much as 375 kg than before midnight.Keywords : composition of the catch, anchovy purse seine, before midnight, after midnight